MASKULINISASI IKAN GAPI (Poecilia reticulata) MELALUI PERENDAMAN INDUK BUNTING DALAM LARUTAN MADU DENGAN LAMA PERENDAMAN BERBEDA - Eko Priyono; Muslim .; Yulisman . (Universitas Sriwijaya, 2013)
ABSTRACT The purpose of this research was to know the influence of dipping time of pregnant guppy in 5 ml.L-1 of honey solution to masculinitation of guppy. The research was conducted on July until October 2012 at Fish Breeding Unit of Batanghari Sembilan Foundation, Indralaya, Ogan Ilir. Research conducted using completely randomized design with four treatments of dipping namely P0 (0 hours), P1 (12 hours), P2 (14 hours), and P3 (16 hours) with three replications. The parameters observed were male percentage, survival rate, and water quality. The result of the current research showed that the dipping time of pregnant guppy in 5 ml.L-1 honey solution gave significant influence on male percentage of guppy larva. The percentages of male guppy from highest to lowest were P0 (69,26%), P1 (76,66%), P2 (52,23%), and P3 (40%). The dipping time of pregnant guppy in 5 ml.L-1 honey solution gave not significant influence on survival rate of guppy larva. Water quality is still in range appropriate to survival rate of guppy. Keywords : Honey, masculinitation, dipping time, male percentage